After the asylum: A Basaglian-informed visin of Recovery-oriented care - Davidson, Larry (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2017)
Prior to his untimely death, Franco Basaglia had envisioned a “next step” for the anti-asylum movement to involve working toward the inclusion of persons with serious mental illnesses in the community activities and settings of their choice. The current status of mental health systems both in the U.S. and in Brazil suggest that this remains a central challenge that continues to require innovative and concerted efforts. In this article, I review three directions of system transformation strategies for promoting community inclusion and full citizenship that Basaglia had foreseen but which he had not lived long enough to pursue in earnest. These include addressing discrimination against persons with mental illness, addressing the role of service users throughout the mental health system, and addressing the social determinants of mental health on a societal scale. While the asylums have been effectively closed and promising work has begun in each of these three areas, there remains much more work to be done in ensuring persons with mental illness a meaningful life in the communities of their choice.